The Bryofauna of Remote Coastal Labrador: including a review of current Canadian records - Boeckner, M.; Collins, M.; Finney-Crawley, J.; Bateman, L. (Zootaxa, 2006)
Nematodes, tardigrades and bdelloid rotifers were identified from moss samples collected from sites near three remote towns in northern, coastal Labrador, Canada. Twenty-three nematode genera, 18 tardigrade species and six rotifer species were identified. All findings were new records for Labrador and many were new records for Canada including three nematode genera (Zeldia Thorne, Daptonema Cobb and Steineria Mikoletzky) and two species of rotifer (Macrotrachela punctata Murray and Macrotrachela aculata Murray). Canadian bryofaunal studies are reviewed and distributional patterns for Canadian taxa are discussed.